2020
DOI: 10.1002/ece3.6898
|View full text |Cite
|
Sign up to set email alerts
|

Melanin‐based ornament darkness positively correlates with across‐season nutritional condition

Abstract: Condition-dependence is a fundamental concept in sexual selection research. Costs of mate choice (in terms of time, energy, and opportunity) necessitate benefits that outweigh these costs. A major group of benefits arises from condition-dependence, which means the adjustment of signals to the physiological state of the individual, as a consequence of the costs of expressing elaborate signal values (Penn & Számadó, 2020). Condition-dependence may link signal expression to the additive genetic background of cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…For the wing, a higher PC1 score corresponds to higher chroma and brightness. The repeatability of spectral variables was calculated using rptR in R (Hegyi et al 2020) and was relatively high between consecutive spectra of the same individuals (Table A1), so we used the mean of the five measurements per body patch in the following analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the wing, a higher PC1 score corresponds to higher chroma and brightness. The repeatability of spectral variables was calculated using rptR in R (Hegyi et al 2020) and was relatively high between consecutive spectra of the same individuals (Table A1), so we used the mean of the five measurements per body patch in the following analyses.…”
Section: Discussionmentioning
confidence: 99%
“…2019, Hegyi et al . 2020), and previous studies have found that outcomes can be affected by sex‐dependent life history strategies and hormone levels (Emaresi et al . 2014, Immonen et al .…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…calcium; 19). In blackcaps ( Sylvia atricapilla ), darkness of melanin-based ornaments positively correlated with nutritional condition across seasons 40 , however, it is not known whether the effect was caused by general diet restriction or restriction of a specific diet component. In addition to the components of the diet, other condition-related factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic processes allow carotenoid‐based coloration to respond to environmental and physiological changes (e.g., Rosenthal et al., 2012 ). Attention has also been drawn to the condition dependence and the resulting information content of melanin‐based coloration (Griffith et al., 2006 ; Hegyi et al., 2020 ; Minias et al., 2019 ; Roulin, 2016 ; Sly et al., 2022 ). Melanin pigments are endogenously synthesized from amino acids and observed correlations between integumentary melanin concentration (perceived as blackness) and body condition have been hypothesized to arise from production or display costs or from pleiotropic genetic effects (Hegyi et al., 2020 ; Roulin, 2016 ).…”
Section: Introductionmentioning
confidence: 99%